Pain, swelling and irritability in the sun: what is the diagnosis?. Issue 2 (21st August 2019) - McGlacken-Byrne, Sinead Mary; Dann, Lisa; Murphy, Annette; Moylett, Edina
Abstract : A 7-year-old boy presented with a 24-hour history of severe burning pain affecting both hands that had started within minutes of playing outdoors. His mother reported that he had been running his hands under cold water and shaking his hands and head to try and relieve the pain. On examination, there was swelling of his hands, eyelids and cheeks. His parents mentioned that his hands and face had 'swollen in the sun' every summer from the age of 2 years. A 3-year-old girl presented with a 2-day history of left upper limb swelling following a day of prolonged sun exposure. Examination revealed non-pitting oedema extending from her left shoulder to hand with no associated tenderness, erythema or rash. Her mother reported six previous episodes of irritability following sun exposure during which she would cry and flap her hands 'for hours'. Oral steroids and antihistamines were prescribed in both cases with little effect. Findings of routine baseline investigations were normal in both cases. A radiograph of the upper limb in the second patient disclosed nothing abnormal. Questions: What is the most likely diagnosis for both patients? Venomous insect bites/stings Erythropoietic protoporphyria IgE-mediated reaction Mixed connective tissue disease Complement deficiency Which investigative approach will be most helpful? Complement function evaluation Physical urticarial evaluation Porphyria work-up Autoantibody screen Immunodeficiency work-up How would you manage these patients? Answers can be found on page 02.